Dynamic Method for Evaluating the Environmental Carrying Capacity of a Chinese Industrial Park - Xu, Linyu; Kang, Peng; Yu, Bing; Xie, Xiaodong (Journal of Environmental Accounting and Management, 2026)
Increased industrialization has heightened the environmental pressure on complex ecosystems in industrial parks and even hindered sustainable development in some regions. Thus, we present an evaluation method for calculating the environmental carrying capacity of an industrial park, which provides a comprehensive evaluation index system for the environmental carrying capacity and environmental pressure. We used this method to conduct a dynamic evaluation of the coupling coordination for the environmental carrying capacity of Fushan Industrial Park in Zhuhai, China. We also simulated the environmental trends based on industrial park planning. The evaluation results showed that the coupling coordination degree exhibited a rapid upward trend from the early stage (2009-2015) of planning to the midstage of planning (2015-2020). In the mid-stage of the planning, the industrial park development was at the mid-level coordination degree. In the mid-late stage of industrial park planning, the coupling coordination degree exhibited a moderate decline, but it still remained at the intermediate coordinated development stage. The price scissors method was used to study the relative change between these stages and the results showed that the relative trend difference degree increased from 0.25 in the early stage of planning to 1.43 in the late stage of planning, which demonstrated that fluctuations occurred in the final stage of planning (2020-2030).